Anti-EMT and anti-fibrosis effects of protocatechuic aldehyde in renal proximal tubular cells and the unilateral ureteral obstruction animal model - Yu-Teng Chang; Mu-Chi Chung; Chi-Hao Chang; Kuan-Hsun Chiu; Jeng-Jer Shieh; Ming-Ju Wu (Taylor & Francis Group, 2022)
Context Protocatechuic aldehyde (PCA) is a natural product that has various benefits for fibrosis.Objective This study evaluated the effects of PCA on renal fibrosis.Materials and methods Epithelial-mesenchymal transition (EMT) was induced by 20 ng/mL transforming growth factor-β1 (TGF-β1), followed by treatment with 1 and 5 μM PCA, in the rat renal proximal tubular cell line NRK-52E. Cell viability, protein expression, and scratch wound-healing assays were conducted. Sprague-Dawley (SD) rats underwent unilateral ureteral obstruction (UUO) surgery for renal fibrosis indication and were treated with 50 and 100 mg/kg PCA for 14 days.Results The IC50 of PCA was appropriately 13.75 ± 1.91 μM in NRK-52E cells, and no significant difference at concentrations less than 5 μM. PCA ameliorated TGF-β1-induced EMT, such as enhanced E-cadherin and decreased vimentin. Fibrotic markers collagen IV and α-smooth muscle actin (α-SMA) increased in TGF-β1-induced NRK-52E. Moreover, PCA reduced TGF-β1-induced migration in the wound-healing assay. Analysis of rat kidneys indicated that PCA reduced UUO-induced hydronephrosis (control: 15.11 ± 1.00%; UUO: 39.89 ± 1.91%; UUO + PCA50: 18.37 ± 1.61%; UUO + PCA100: 17.67 ± 1.39%). Protein level demonstrated that PCA not only decreased vimentin expression and enhanced E-cadherin expression, but inhibited UUO-induced collagen IV and α-SMA upregulation, indicating that it could mitigate EMT in a rat model of UUO-induced renal fibrosis.Discussion and conclusions This study suggested that PCA decreases TGF-β1-induced fibrosis and EMT in vitro and in vivo. These findings demonstrate pharmacological effects of PCA and might be a potential strategy for the prevention of organ fibrosis in clinics.